Recombinant Factor VIIa–Mediated Activation of Prothrombin Complex Concentrates: Studies on the Comparison of NovoSeven With a Biosimilar Product. (April 2017) - Sadeghi, Nasiredin; Iacobelli, Massimo; Vaziri, Behroz; Kahn, Daniel; Hoppensteadt, Debra; Guler, Nil; Fareed, Jawed
Recombinant factor VIIa (rFVIIa) is used in the management of bleeding in patients with hemophilia. A generic biosimilar version of NovoSeven is also developed (AryoSeven). To compare the activation profile of NovoSeven and AryoSeven, 2 commercially available protein complex concentrates (PCCs) were used. Profilnine activated by RecombiPlasTin 2G resulted in conversions of prothrombin to prethrombin and thrombin at 5 to 30 minutes. However, addition of rFVIIa at final concentration range of 0.25 to 0.5 µg/mL to the same mixture resulted in total conversion of prothrombin to thrombin with a doublet at 36 kDa. Recombinant factor VIIa alone did not generate thrombin in native Beriplex, and the addition of rFVIIa to Beriplex failed to generate thrombin. Beriplex activated by RecombiPlasTin 2G resulted in complete conversion of prothrombin to thrombin. Both NovoSeven and AryoSeven exhibited similar activation profiles. These studies indicate that the activation of PCCs by both rFVIIa preparations results in comparable generation of thrombin.